2017
DOI: 10.1111/jocn.13905
|View full text |Cite
|
Sign up to set email alerts
|

Palestinian community perceptions of do‐not‐resuscitation order for terminally Ill patients: A qualitative study

Abstract: Our findings provide a unique understanding that there is a general misunderstanding among our participants regarding the do-not-resuscitate order. Further research with policymakers and stakeholders is still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Higher educational levels among nurses meant having more confidence to deal with patients’ problems in clinical nursing practices [ 45 ]. Prior studies have shown that religious beliefs are a significant factor in forming caregivers’ and health care providers’ viewpoints about DNR decisions [ 46 , 47 ]. This significance is because religious beliefs play an essential role in the lives of many people since spiritual and ethical issues are usually aroused or strengthened as patients near end-of-life, as well as nurses on nursing practice behaviors toward the end-of-life care [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher educational levels among nurses meant having more confidence to deal with patients’ problems in clinical nursing practices [ 45 ]. Prior studies have shown that religious beliefs are a significant factor in forming caregivers’ and health care providers’ viewpoints about DNR decisions [ 46 , 47 ]. This significance is because religious beliefs play an essential role in the lives of many people since spiritual and ethical issues are usually aroused or strengthened as patients near end-of-life, as well as nurses on nursing practice behaviors toward the end-of-life care [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…No other more recent studies have been conducted in Israel that provide evidence to whether this assumption is true. However, several studies in Moslem countries found a lack of support for DNAR among physicians 30 and lay people 31 due to a conflict with religious Islamic beliefs and the legal system. Such cultural constraints might trigger healthcare providers into performing slow codes when religious values are in conflict with professional training.…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the literature also suggests that other factors may influence people's perceptions toward FWR are education, training, and experience [53][54][55][56][57][58][59][60].…”
Section: Specific Literature Review On Fwr and Research Gapsmentioning
confidence: 99%